2020
DOI: 10.3389/fonc.2020.00310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fresh Frozen Tissue With Formalin-Fixed Paraffin-Embedded Tissue for Mutation Analysis Using a Multi-Gene Panel in Patients With Colorectal Cancer

Abstract: Background: Next generation sequencing (NGS)-based multi-gene panel tests have been performed to predict the treatment response and prognosis in patients with colorectal cancer (CRC). Whether the multi-gene mutation results of formalin-fixed paraffin-embedded (FFPE) tissues are identical to those of fresh frozen tissues remains unknown.Methods: A 22-gene panel with 103 hotspots was used to detect mutations in paired fresh frozen tissue and FFPE tissue from 118 patients with CRC.Results: In our study, 117 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
(44 reference statements)
0
50
0
Order By: Relevance
“…On the other hand, frozen tissues allow Fig. 3 Sensitivity analysis showing the impact of exclusion of any study on the summary effect better DNA preservation, but require constant lowtemperature maintenance [50]. In the present study, the HPV detection rate was slightly higher when frozen tissues were used.…”
Section: Publication Biasmentioning
confidence: 59%
“…On the other hand, frozen tissues allow Fig. 3 Sensitivity analysis showing the impact of exclusion of any study on the summary effect better DNA preservation, but require constant lowtemperature maintenance [50]. In the present study, the HPV detection rate was slightly higher when frozen tissues were used.…”
Section: Publication Biasmentioning
confidence: 59%
“…Secondly, the samples were in FFPE form and were not fresh frozen tissue (FFT). Quality of PCR might be slightly higher in FFT samples compared to FFPE; however, the difference is trivial and non-significant in many cases [35,36]. For instance a previous study declared the superiority of fresh tissue samples over FFPE [27].…”
Section: Discussionmentioning
confidence: 96%
“…In a cohort of 10 paired metastatic liver CRC specimens, a high mutational concordance was observed when 212 amplicon regions in 48 cancer-related genes were sequenced, revealing 21 identical mutation calls and only two differing mutations [ 33 ]. Furthermore, Gao et al conducted an extensive study using a 22-gene panel detecting 103 hotspot mutations in paired FFPE and fresh-frozen primary CRC tissues from 118 patients [ 34 ]. The investigators identified a concordance rate ranging from 73.8% to 100% and highlighted that important differences exist between the two tissue types.…”
Section: Discussionmentioning
confidence: 99%